PEMBERIAN KOMBINASI PUPUK ORGANIK HAYATI DAN PUPUK NITROGEN SINTETIK UNTUK PERBAIKAN SIFAT KIMIA TANAH, PERTUMBUHAN DAN HASIL SAWI - melly febriyanti (Jurnal Agroteknologi dan Pertanian (JURAGAN), 2025)
The continuous use of chemical fertilizers can lead to a decrease in soil quality and environmental pollution. Biological organic fertilizer (BOF) is commonly used to improve soil chemical properties. However, the fertilizer release nutrients slowly so that the effect is not significant mainly at early stage of plant growth. Consequently, farmers have not been interested to use the fertilizer. Biological organic fertilizers are organic fertilizers enriched with functional microbes, so that the combination of synthetic fertilizers and biological organic fertilizers can increase the availability of nutrients, stimulate growth and improve soil properties. However, the effectiveness of the biofertilzer to improve soil chemical properties and substituting for synthetic N fertilizer have not been evaluated intensively. The experiment was carried out in two stages, namely an incubation experiment and a field experiment for two months in December 2018 - January 2019 The study aimed to determine changes in soil chemical properties under the application of biofertilizer and determine the balance of N and BOF fertilizers for growth and yield of mustard biomass. The incubation experiment assigned Completely Randomized Design (CRD) with 5 treatements and 3 replications. The treatment was the application of biofertilizer at doses of 0, 2.4, 4.6, 7.0, 9.2 tons/ha. Meanwhile, the field experiment used Randomized Complete Block Desugn (RCBD) with 5 treatments with 3 replications. The treatments were 100% N + 0% BOF, 75% N + 25% BOF, 50% N + 50% BOF, 25% N + 75% BOF, 0% N + 100% BOF, 0% N + 0% BOF. The results showed that the application of biological organic fertilizers increased soil pH, total N and decreased organic C and C/N ratios. The substitution of synthetic N and BOF increased plant height, LD 33, ILD 28, ILD 33, LTR 33, LTR 40, plant fresh weight and fresh weight per plot. In summary,the use of biological organic fertilizers is able to substitute for the N from synthetic fertilizer for the growth of mustard and can improve the soil properties, leading to an increase in mustard yields environment and lead to an increase in mustard plant yields.